2018
DOI: 10.23937/2377-4630/1410061
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin in Topical Formulations Augments Pain Reduction of Other Analgesics in the Treatment of Neuropathic Pain

Abstract: Topical analgesic formulations are gaining interest for the treatment of peripheral neuropathic pain since the beginning of 2000. Advantages of topical analgesics over oral medication are the absence of systemic side effects and drug-drug interactions, higher concentrations of active compound at the pain area, fast onset on action, improvement of compliance, and no risk of abuse. In many peripheral neuropathic pain states the pain area is small and thus topical analgesics are suitable. Most patients experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This study demonstrated that topical analgesics could be a beneficial therapeutic alternative for most of chronic pain patients but there still existed some patients who did not benefit from it having an insignificant reduction of pain levels. 33 The present research work attempts to utilize machine learning in the context of an individualized medicine approach for chronic pain therapies. In specific, focus is given on a topical analgesics therapy and a machine learning approach is deployed to predict the outcomes of the therapy given the demographic and clinical profile of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that topical analgesics could be a beneficial therapeutic alternative for most of chronic pain patients but there still existed some patients who did not benefit from it having an insignificant reduction of pain levels. 33 The present research work attempts to utilize machine learning in the context of an individualized medicine approach for chronic pain therapies. In specific, focus is given on a topical analgesics therapy and a machine learning approach is deployed to predict the outcomes of the therapy given the demographic and clinical profile of the patients.…”
Section: Introductionmentioning
confidence: 99%